2014
DOI: 10.1088/0957-0233/25/6/064014
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-aided investigation of beam hardening induced errors in CT dimensional metrology

Abstract: Industrial x-ray computed tomography (CT) systems are being increasingly used as dimensional measuring machines. However, micron level accuracy is not always achievable, as of yet. The measurement accuracy is influenced by many factors, such as the workpiece properties, x-ray voltage, filter, beam hardening, scattering and calibration methods (Kruth et al 2011 CIRP Ann. Manuf. Technol. 60 821–42, Bartscher et al 2007 CIRP Ann. Manuf. Technol. 56 495–8, De Chiffre et al 2005 CIRP Ann. Manuf. Technol. 54 479–82,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Suppes et al [11] reasoned the grey value inhomogeneity caused by beam hardening influenced the position of the determined surface; experimental data showed correcting for beam hardening reduced both errors in form and length measurements. The group of Dewulf et al [12][13][14][15] have shown that changes in X-ray path length and the coefficients of a linearisation polynomial can influence dimensional measurements. All the aforementioned results support the premise that beam hardening influences dimensional measurements; however, an explanation as to how this influence occurs has yet to be given.…”
Section: Previous Workmentioning
confidence: 99%
“…Suppes et al [11] reasoned the grey value inhomogeneity caused by beam hardening influenced the position of the determined surface; experimental data showed correcting for beam hardening reduced both errors in form and length measurements. The group of Dewulf et al [12][13][14][15] have shown that changes in X-ray path length and the coefficients of a linearisation polynomial can influence dimensional measurements. All the aforementioned results support the premise that beam hardening influences dimensional measurements; however, an explanation as to how this influence occurs has yet to be given.…”
Section: Previous Workmentioning
confidence: 99%
“…36 Effects are more pronounced in bone because of the high calcium content 37 and subsequent absorption of x-rays. 38 Attempts to optimize corrections for beam hardening exist in clinical applications 37 and in industrial metrological applications. [38][39][40] Investigators of another study 41 compared results for CT LO , oblique CT, and CT TO images of a human ankle prosthesis implanted in a stifle joint of a pig.…”
Section: Discussionmentioning
confidence: 99%
“…38 Attempts to optimize corrections for beam hardening exist in clinical applications 37 and in industrial metrological applications. [38][39][40] Investigators of another study 41 compared results for CT LO , oblique CT, and CT TO images of a human ankle prosthesis implanted in a stifle joint of a pig. In that study, 41 measurements for CT TO images were less accurate than measurements for CT LO images.…”
Section: Discussionmentioning
confidence: 99%
“…The final step is a reconstruction of the image by using this effective energy to generate monochromatic projection data (Thomsen et al 2015). This method if chosen to be applied requires knowledge about the detector efficiency and the energy spectrum MC simulation which has been extensively used for investigation of beam hardening artifact in many studies such as Arunmuthu et al (2013), Lifton et al (2013), Ramakrishna et al (2006), Sahebnasagh et al (2012), Tan et al (2014), Thomsen et al (2015) and Yan et al (2000). It has high precision and is very flexible regarding changes in the beam geometry, sample composition, objects geometry and densities.…”
Section: Monte Carlo Simulation Correction Methodsmentioning
confidence: 99%